STATUS REPORT ON MUSHROOM BASED NUTRACEUTICAL PRODUCTS IN THE MARKET - Srivastava, Anuradha; Attri, Brij Lal; Sharma, Ved Parkash (Mushroom Research, 2020)
Mushrooms have been used for medicinal and food purposes since times immemorial. Many pharmaceutical substances with potent and unique properties have been isolated from mushroom and distributed worldwide.During the past decade, there has been a major expansion in the industries involved in providing these substances. These products have also been called: nutraceuticals, phytochemicals or functional foods.Many commercial nutraceutical products from medicinal mushrooms are available worldwide. These mushroom health supplements are marketed in the form of powders, capsules or tablets made of dried fruiting bodies, extracts of mycelium with substrate, biomass or extract from liquid fermentation. These products include water or alcohol extracts, concentrates, and powders in bulk or tablet form. Besides these some functional beverages from medicinal mushrooms such as mushroom tea and coffee which are rich in antioxidants and boost the immune system are also available in the market and are widely acceptable.